Bulk metallic glasses and their composites additive manufacturing and modeling and simulation - Rafique, Muhammad Musaddique Ali (De Gruyter STEM., 2021)
"The book provides a comprehensive state-of-the-art review on the topic of bulk metallic glass matrix composites and understanding of mechanisms of development of composite microstructure. It discusses mechanisms of formation and toughening both during conventional casting routes and additive manufacturing. The second edition encompasses new studies and highlights advancement in mechanical properties, characterization, processing and applications."--Publisher's website